ANALISIS KESIAPAN PELEPASLIARAN PASANGAN OWA JAWA DI PUSAT REHABILITASI PRIMATA JAWA (PRPJ) THE ASPINALL FOUNDATION - Reni Nurdianti; Ana Widiana; Risda Arba Ulfa (Gunung Djati Conference Series, 2023)
The Javan gibbon (Hylobates moloch) is one of the endemic primates that are protected on the island of Java. The results of research and surveys show that the Javan gibbon population in its natural habitat has a declining trend. Conservation efforts that can be done to rebuild the Javan gibbon population in the wild are by releasing them. For release, careful preparation and consideration is needed because the Javan gibbon has a high level of sensitivity to disturbance. This research was conducted at the Javan Primate Rehabilitation Center (JPRC) The Aspinall Foundation with the aim of knowing the release readiness status of the Javan gibbon pair based on 4 release criteria consisting of permanent partner readiness, daily activity readiness, health readiness and ability to consume natural food. The study was conducted on two pairs of Javan gibbons targeted for release, namely Udin-Lola and Joy-Bobby. Observations were made from January to February 2022 using the ad libitum method and scan sampling with an interval of 5 minutes . The results showed that based on 4 criteria for release, both partners were declared to have met the criteria for release, except for the status of the ability to consume natural food. During the observation, copulation activity was not observed, but the Udin-Lola pair was seen several times carrying out pre-copulation activities. Based on the value of readiness for release, the Udin-Lola pair were categorized as ready to be released into the wild with scores of 74.2. Meanwhile, the Joy-Bobby couple is not ready to be released with a score of 68.6.